Sustained censorship in MM (2026-02) (Myanmar) - Voidly (2026)
CRITICAL severity censorship detected in Myanmar. Confidence: 80%. Data sourced from OONI.
Censorship Incident ID: MM-2026-0336
Keywords: censorship; MM; censorship; critical